Contesting Patriarchy Online: Rethinking Feminist Digital Activism under Surveillance in Indonesian Context - Wibisono, Rizky Bangun; Ayunina, Aldisa Qurrota; Hasanah, Mauidhotul; Nurhaliza, Naswa Annyce (UIN Sunan Ampel Surabaya, 2025)
Feminist digital activism has become increasingly vital in confronting gendered repression in online spaces, especially in Indonesia, where state regulation, corporate platform control, and patriarchal norms converge. While prior research has addressed surveillance, algorithmic bias, and legal repression under laws like the Information and Electronic Transactions Law (UU ITE), less is known about how feminist movements in the Global South collectively resist these forces. This study fills that gap through a qualitative-interpretive approach grounded in critical feminist theory and Nancy Fraser’s justice framework—redistribution, recognition, and representation. Drawing on secondary sources including activist publications, academic works, and legal documents, the paper analyzes how Indonesian feminist actors navigate digital criminalization, SLAPP (Strategic Lawsuits Against Public Participation), and algorithmic exclusion. Findings show that feminist digital activism is not merely reactive but proactive, with strategies ranging from gender-aware digital literacy and legal reform advocacy to transnational solidarity and the development of community-run digital infrastructures. These actions reframe online feminist activism as structural resistance rooted in democratic participation. While limited by the absence of primary ethnographic data, this research offers a critical Global South feminist lens on digital justice and underscores the importance of collective agency in building inclusive and gender-just digital futures.